Análise dos efeitos das variações das características do ambiente construído na percepção dos usuários - Penteado, Ana Paula Bonini (2015)
The conscious and unconscious perception of the individual has a significant influence on the user's satisfaction with the built environment. When it comes to human perception, studies show that 75% of what the individual perceives refer to the visual system, 20% is related to sound perception and only 5% come from other senses such as touch and smell. In this sense, the objective of this work is to show how variations in built environment characteristics, associated with sight and hearing, influence the individual's perception, translated into positive or negative feelings. In this way, it will be possible to assess how the perceived characteristics of the built environment can influence users towards the environment. When perceiving an environment, each individual makes it in a distinct way. The research aims to identify how the user perception influences the way to observe and feel the environment and how these aspects impact the design features. By identifying some design features and some sounds related to the built environment, a composed experiment with a questionnaire was elaborated, contending nine images and four sounds that enclose these characteristics. The questionnaire was applied in students of the courses of Civil Engineering and Architecture and Urbanism of the Federal Technological University of the Paraná, in the months of November and December of 2014. With the application of the experiment, by associating the images and the sounds, with positive and negative affection of the PANAS Scale (Scale of Positive and Negative Affection), it was concluded that the individual's perception in certain environmental characteristics, provide increased feelings connected to the positive affects and in other cases, the negative affects. It was also analyzed the perception of the feelings and design features in relation to vocational guidance and in relation to gender. Through thisresearch, , it could be perceived which features have more impact on positive and negative feelings and which guarantee and provide comfort to the users of built environments.